Effect of sodium phosphate supplementation on repeated high-intensity cycling efforts - Brewer, C. P.; Dawson, B.; Wallman, K. E.; Guelfi, K. J. (Journal of Sports Sciences, 2015)
Limited research has investigated how sodium phosphate supplementation affects exercise performance typical of athletic competition and whether any effects linger in the short term. This study examined the effect of sodium phosphate supplementation on a cycling protocol consisting of repeated-sprint (4 sets of 6 × 15 s) and time-trial (2 × 5 min) efforts on day 1 and 4 post-loading. Trained male cyclists (O2peak 5.3 L/min) were randomised to 6 days of sodium phosphate supplementation (50 mg/kg·fat-free-mass.day; n = 7) or placebo (n = 10). Performance was assessed at baseline and 1 and 4 days post-supplementation on an air-braked cycle ergometer. Compared with baseline, the sodium phosphate group recorded significantly improved (P < 0.05) work and mean power output values in both the sprint (baseline, 259 kJ/719 W; day 1, 271 kJ/754 W; day 4, 271 kJ/753 W) and time-trial (baseline, 225 kJ/374 W; day 1, 235 kJ/398 W; day 4, 236 kJ/393 W) aspects of the performance test post-loading. In the placebo group, no differences (P > 0.05) in total work or power output were noted in response to supplementation. In summary, sodium phosphate supplementation improved repeated-sprint and time-trial cycling efforts both 1 and 4 days post-loading in trained cyclists.